Systemische Amyloidosen - Schönland, Stefan; Blank, Norbert; Kristen, Arnt; Beimler, Jörg; Ganten, Tom M.; Hegenbart, Ute (Der Internist, 2012)
Amyloidoses are rare protein folding disorders, in which proteins are deposited as insoluble fibrillar aggregates due to a conformational change. This can occur in a local or systemic form. Systemic amyloidoses are life-threatening complications of monoclonal gammopathy, chronic inflammatory diseases or within hereditary diseases. The causative treatment of amyloidosis is the reduction of the amyloid precursor protein by chemotherapy, anti-inflammatory treatment, or liver transplantation. Early diagnosis of the disease is essential in order to effectively treat patients and avoid further deterioration of organ functions.
Gesehen am 11.07.2018
Online publiziert: 27. Oktober 2011